Lactate minimum is valid to estimate maximal lactate steady state in moderately and highly trained subjects - Knoepfli-Lenzin, C.; Boutellier, U. (The Journal of Strength and Conditioning Research, 2011)
Some evidence exists that the determination of maximal lactate steady state (MLSS) with lactate minimum (LM) in highly trained athletes is not as accurate as in less trained athletes. Therefore, we compared power output at LM with power output MLSS in moderately up to highly trained subjects. 63 subjects performed a test on a cycle ergometer to determine power output at LM and 3 or more constant-load tests of 30 minutes to determine power output at MLSS. Mean power output at LM (245 ± 29 W; mean ± SD) was slightly lower than power output at MLSS (255 ± 32 W). The correlation between power output at MLSS and LM was high, and the regression line runs parallel to the line of identity showing that the results of highly trained subjects agree with the results of less trained subjects (LM and MLSS r = 0.867, p < 0.001). The modified blood-lactate kinetic in highly trained athletes compared with less trained persons does not impair accuracy at LM. Therefore, we suggest LM as a valid and meaningful concept to estimate power output at MLSS in 1 single test in moderately up to highly trained athletes.